2009
DOI: 10.1016/j.mrfmmm.2009.01.011
|View full text |Cite
|
Sign up to set email alerts
|

The effects of in utero irradiation on mutation induction and transgenerational instability in mice

Abstract: It is well known that the developing embryo is especially sensitive to ionising radiation. However, to date little is known about the long-term effects of in utero exposure on mutation rates during adulthood. To evaluate the effects of in utero irradiation on mutation induction and transgenerational instability, BALB/c pregnant mice (Theiler stage 20, 12 days of gestation) were exposed to 1 Gy of acute X-rays. The in utero exposed 8-week-old males and females were mated to control partners. To evaluate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 35 publications
7
56
0
Order By: Relevance
“…These data are in line with the results of previous studies on the transgenerational effects of paternal irradiation showing significantly increased ESTR mutation frequencies in the germline and somatic tissues in the offspring of irradiated male mice (8,9,24); the same tissue-wide destabilization of the F 1 genome has been demonstrated in the present study. Moreover, other recent studies have shown a similarly elevated mutation rate in the offspring of irradiated male mice at the alleles derived from exposed and nonexposed parents (7,8,25); the same holds for the offspring of anticancer drug-treated males.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These data are in line with the results of previous studies on the transgenerational effects of paternal irradiation showing significantly increased ESTR mutation frequencies in the germline and somatic tissues in the offspring of irradiated male mice (8,9,24); the same tissue-wide destabilization of the F 1 genome has been demonstrated in the present study. Moreover, other recent studies have shown a similarly elevated mutation rate in the offspring of irradiated male mice at the alleles derived from exposed and nonexposed parents (7,8,25); the same holds for the offspring of anticancer drug-treated males.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, according to the results of our previous studies, transgenerational instability in the offspring of irradiated male mice is an epigenetic phenomenon (7)(8)(9)). This conclusion is based mainly on the fact that vast majority of the F 1 offspring show similar levels of instability in numerous tissues (8).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This phenomenon has also been observed in male germ cells [de Boer et al, 2010]. Spermatogonial irradiation causes delayed genomic instability in descendant sperm [Sailer et al, 1995;Haines et al, 2001Haines et al, , 2002Cordelli et al, 2003] as well as in the progeny of irradiated male parents in rodents [Baulch and Raabe, 2005;Barber and Dubrova, 2006;Barber et al, 2009] and humans [Aghajanyan et al, 2011]. Remodeling of chromatin domains and nuclear matrix during spermiogenesis and in the zygote has been suggested to play a role in these phenomena [de Boer et al, 2010], but how and when they operate is still unclear.…”
Section: Introductionmentioning
confidence: 93%
“…When tissues from the offspring of the directly irradiated animals were investigated, it was revealed that in contrast to paternal irradiation, maternal exposure did not affect the genomic stability of their offspring. It is possible that even though the epigenetic marks of foetal irradiation can survive developmental reprogramming in both males and females, and lead to genomic instability during adulthood, the failure of irradiated females to pass an instability signal to their offspring to be associated with early postfertilisation events (Barber et al, 2009). …”
Section: Transgenerational Instabilitymentioning
confidence: 99%